A NEW CHARACTERIZATION OF SPORADIC SIMPLE GROUPS - He, Li-Guan; Chen, Gui-Yun; Xu, Hai-Jing (Italian Journal of Pure and Applied Mathematics, 2013)
Let G be a finite group, k1(G) denote the largest element order of G, and k2(G) the second largest element order. In this paper, we show that each sporadic simple group G can be uniquely determined by the order of G and ki(G), where i ≤ 2.